2020
DOI: 10.1007/s40123-020-00253-x
|View full text |Cite
|
Sign up to set email alerts
|

Intra-Operative Mitomycin-C as Adjuvant Therapy in External and Endonasal Dacryocystorhinostomy: Systematic Review and Meta-Analysis

Abstract: Purpose: To evaluate the effect of mitomycin-C (MMC) on the success of external (Ex-DCR) or endoscopic dacryocystorhinostomy (En-DCR). Method: A systematic review of randomized clinical trials of Ex-or En-DCR with and without the use of MMC to treat primary acquired nasolacrimal duct obstruction (NLDO) was done. Two authors independently searched six databases from 1990 to 2019, using the terms ''dacryocystorhinostomy'' and ''mitomycin-C.'' Statistical and meta-analyses were performed using RevMan 5.3 software… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…If the latter seems to improve the final result even if no significant influence has been noted, [38][39][40] mitomycin C, an anti-fibroblasts proliferation agent that can be applied in different concentration, timing and modalities, presents an unclear role on the final outcome making its usage not standardized. [34][35][36][37] Both results of these adjunctive therapies have been confirmed by our analyses that, when feasible, did not find a significant influence regarding its use.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…If the latter seems to improve the final result even if no significant influence has been noted, [38][39][40] mitomycin C, an anti-fibroblasts proliferation agent that can be applied in different concentration, timing and modalities, presents an unclear role on the final outcome making its usage not standardized. [34][35][36][37] Both results of these adjunctive therapies have been confirmed by our analyses that, when feasible, did not find a significant influence regarding its use.…”
Section: Discussionsupporting
confidence: 76%
“…3 If considering the potential influencing factors on the outcomes of these techniques, several studies have highlighted the role of MMC and silicone stenting, which in some cases seems to improve the success rate, with no unanimous consensus achieved. [34][35][36][37][38][39][40] Additionally, recent reviews have demonstrated that, neither the possible combinations of post-operative therapies (e.g. oral antibiotics, nasal/ocular steroids or nasal/ocular antibiotics), nor the type of surgery and mucosal flaps, have a significant influence on the final surgical result.…”
Section: Discussionmentioning
confidence: 99%
“…mitomycin C, oral antibiotics (ABT), nasal steroids or ocular steroids). [33][34][35] As a result, in our cohort, we did not apply mitomycin C, but we do prescribe post-operative antibiotic-steroid eye drops and bicanalicular stenting in all cases.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, considering post-surgical therapy, different possibilities have been discussed in the literature, both for postoperative medical therapy and bicanalicular stenting. Nevertheless, with the current data available regarding END-DCR, no difference is noted regarding either lacrimal stenting [34][35][36] or medical therapies (e.g., mitomycin C, oral antibiotics (ABT), nasal steroids or ocular steroids) [37][38][39][40]. As a result, in our series, we do not apply mitomycin C, but we do prescribe post-operative oral ABT and antibiotic-steroid eye drops; bicanalicular stenting was placed in only selected patients (2/14) in which extensive fibrosis was noted as failure of the primary surgical approach.…”
Section: Discussionmentioning
confidence: 99%